Factors that impact the uptake of mobile banking adoption in South Africa - Mabunda, Steward (University of the Witwatersrand, Johannesburg, 2023)
M-banking is poised to overcome the traditional banking channels such as the Internet, ATM and branch banking and become the mainstream banking option for the sub-Saharan African and global community. The Covid-19 pandemic has reached its peak ushering in the rapid development of digital banking across developing and developed economies. And that prompted the reason for this study. The cross-sectional investigation used a self-administered online survey questionnaire that was distributed to the participants across 9 South Africa and used a modified Technology Acceptance Model consisting of Subjective Norm, Facilitating Conditions, Perceived Usefulness and Perceived Ease of Use to determine the factors that impact the adoption of m-banking. The findings are in line with previous researchers in other parts of the global economy and further studies are advised in the African continent
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: M-banking Technology Acceptance Model; Mobile Banking Adoption; Developing Countries; UCTD; SDG-8: Decent work and economic growth